Gas chromatography coupled to time‐of‐flight mass spectrometry using parallel electron and chemical ionization with permeation tube facilitated reagent ion control for material emission analysis. (19th January 2023) - Bräkling, Steffen; Hinterleitner, Christina; Cappellin, Luca; Vetter, Marleen; Mayer, Ingo; Benter, Thorsten; Klee, Sonja; Kersten, Hendrik
Abstract : Rationale: Volatile organic compounds (VOCs) emitted by an artificial leather part for car interiors are determined using GC–MS (gas chromatograph coupled to a mass spectrometer) using simultaneous electron and chemical ionization (EI&CI). A device for swift reagent ion switching in CI mode between consecutive runs is presented. Methods: VOCs emitted from the investigated material were sampled onto Tenax® absorption tubes using micro emission chambers and subsequently injected into the GC through thermal desorption. The detector was a time‐of‐flight mass spectrometer (TOFMS) simultaneously operating in EI and CI modes during a single chromatographic run. A custom permeation tube setup allowed for swift selection between various reagent ions in CI mode, e.g., [N2 H] +, [H3 O] +, [(H2 O)2 H] +, and [NH4 ] + . Results: Different reagent ions are swiftly selectable between single GC runs without hardware changes. Differences in precursor ion survival yields and the selectivity of the various reactants were carefully assessed. Several examples for the improved identification of unknown compounds with the available complementary and comprehensive EI&CI data set are demonstrated for a relevant material emission application. Conclusion: The presented technique provides additional value to the standard GC‐EI/MS procedure commonly used for material emission characterization. It allows for a non‐targeted analysis approach with moderate analysis time.